DATA-DRIVEN MANAGEMENT OF SOCIAL MEDIA ADVERTISING: THEORY AND PRACTICE (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the management of social media advertising in enterprises through data analytics. The study explores methods for optimizing advertising campaigns on Facebook, Instagram, Telegram, and YouTube based on data-driven approaches, including audience targeting, engagement analysis, and techniques for improving ROAS (Return on Ad Spend). Against the backdrop of rapid growth in social media users in Uzbekistan, the necessity of applying platform-specific analytics tools for local businesses is substantiated. The research findings demonstrate that data-driven social media management can increase advertising ROAS by 2.5–4 times and reduce the Cost per Lead (CPL) by 30–45%.